Morphological effects on the selectivity of intramolecular versus intermolecular catalytic reaction on Au nanoparticles. Issue 23 (2nd June 2017) - Wang, Dan; Sun, Yuanmiao; Sun, Yinghui; Huang, Jing; Liang, Zhiqiang; Li, Shuzhou; Jiang, Lin
Abstract : An active catalyst of spine-like Au nanoparticle with controlled morphological effects presented high selectivity for the hydrogenation reaction of aromatic nitro compounds. Abstract : It is hard for metal nanoparticle catalysts to control the selectivity of a catalytic reaction in a simple process. In this work, we obtain active Au nanoparticle catalysts with high selectivity for the hydrogenation reaction of aromatic nitro compounds, by simply employing spine-like Au nanoparticles. The density functional theory (DFT) calculations further elucidate that the morphological effect on thermal selectivity control is an internal key parameter to modulate the nitro hydrogenation process on the surface of Au spines. These results show that controlled morphological effects may play an important role in catalysis reactions of noble metal NPs with high selectivity.